Mecz piłki nożnej artystów! (Słupsk : [wydawca nieznany], 1946)
Afisz informujący o meczu na Stadionie Miejskim w Słupsku.
Keywords: Piłka nożna -- Polska -- Słupsk -- 1945-1970 -- druki ulotne; Słupsk (Polska) -- 1945-1970 -- druki ulotne; Słupsk (Polska) -- 1945-1970 -- źródła